Traditional methods for managing illness in newborns and infants in an Arab society. (7th March 2019) - Arabiat, D.H.; Whitehead, L.; AL Jabery, M.; Towell‐Barnard, A.; Shields, L.; Abu Sabah, E.
Abstract : Aim: This study explored self‐management practices in relation to traditional methods for managing illness in newborns and infants and the implications of these practices on infant health. Background: Self‐medication with folk remedies is believed to have short‐ and long‐term impacts on well‐being. Little is known about how mothers in Arab societies used their traditional beliefs and practices in self‐managing their newborns' and infants' health. Methods: Data were collected from five focus groups using open‐ended questions with 37 mothers. Participants were selected using snowball sampling and were recruited from four different cities in Jordan between June 2016 and August 2016. Ethical approval: All identifying information regarding the study participants has been omitted, and this study was approved by the Academic Research Committee at the University of Jordan. Findings: Mothers were more willing to try herbal remedies, traditional massage and certain foods to self‐manage their infants' health. Folk remedies were not restricted to traditions handed down through generations, but included a representation of newly emerged trends towards 'safety' or 'nature'. Conclusions: While the use of folk remedies have been handed down generations as customs, today, virtual support groups and social media provide modern resources for folk remedies' promotion in care and self‐management. Implications for nursing and health policy: Nursing and health policymakers can use our findings for planning and developing strategies and health policies that increase public awareness about adverse health effects associated with herbal remedies. Such strategies are likely to be facilitated through partnerships between nursing and midwifery education institutions, antenatal clinics and social media in the region.